UPAYA PENERAPAN METODE JOB SAFETY ANALISIS UNTUK MENGIDENTIFIKASI POTENSI KECELAKAAN KERJA SAAT PELAKSANAAN CARGO OPERATION DI KAPAL MV. HODASCO 19 - Teddy Palguna Januarta, I Kadek; Imam Firdaus, Muhamad; Nofandi, Faris; Haryanto, Tri (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
Cargo operations on aging general cargo vessels like MV. Hodasco 19 (built 1984) face heightened occupational accident risks due to equipment degradation, unsafe worker behaviors, and gaps between ISM Code procedures and field practices. This study aims to apply Job Safety Analysis (JSA) to identify accident potentials during cargo operations and formulate preventive measures. Employing a descriptive qualitative approach, purposive sampling targeted the Chief Officer as key informant from MV. Hodasco 19 crew during Teluk Bayur-Belawan routes. Instruments included semi-structured interviews, observation sheets, and photographic documentation, analyzed via Miles and Huberman's reduction-presentation-conclusion model with risk matrix assessment. Findings reveal 75% of activities (lifting operations, wire rope inspection, worker positioning, night operations) classified as high risk (scores 15-20). Conclusions recommend mandatory written JSA implementation, crew-stevedore training, and routine equipment inspections to achieve zero accidents per maritime standards.